Godrej Appliances : enhancing value and brand image - Bhavani Shankar, S.; Bhatta, N. M. K. (London : NeilsonJournals Publishing, 2016)
While reviewing the performance of 2015-16 with the previous two years, Kamal Nandi, Business Head and in charge of Godrej Appliances Division (GAD), was delighted that the strategies implemented in the last 3 years were giving positive results. As he was preparing for another year-end strategy team meeting to ensure the long term sustainability of GAD, he was concerned about how to continue enhancing customer value. His strategy team, involving heads from all functions, had proved their mettle over the years and the results were there to see. Despite increasing competition, he was counting on the (i) culture of innovation, (ii) number of products launched, (iii) increased emphasis on modern retail and (iv) promotion through non-traditional media to ensure Godrej achieved its goal, "to be amongst the top three appliance companies in India by 2020".
Originally Published InShankar, S. B., & Bhatta, N. M. K. (2016). Godrej Appliances: Enhancing value and brand image. Journal of International Business Education, 11(1), 243-266. JIBE11-0CS5.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nandi, Kamal; Godrej Appliances Division; Branding (Marketing); Total quality management; Organizational effectiveness; Marketing; Customer relations